Qur’anic Perspectives on Mustadh‘afin: Gendered Oppression and Women’s Empowerment in Contemporary Indonesia - Siregar, Nina Sari; Simamora, Nur Aisah (Jurnal Pemikiran Islam, 2025)
This article investigates the forms of mustadh‘afin (systemic oppression) experienced by women, as reflected in selected Qur’anic verses, and analyzes their relevance to the realities of contemporary Indonesian society. Filling a gap in previous scholarship, which often separates gender analysis from Qur’anic interpretation, this study adopts a gender-aware thematic approach (tafsir maudhu‘i) and draws on both classical and contemporary exegesis, including Al-Kassyaf, Tafsir Ibn Kathir, Al-Maraghi, and Al-Misbah. The analysis focuses on QS. An-Nisa [4]: 75, 97, 98; QS. Al-Anfal [8]: 26; and QS. Al-Qashash [28]: 4–5, all of which frame mustadh‘afin as a condition produced by structural marginalization, limited access to rights, and deep-seated gender stereotypes. In present-day Indonesia, such patterns of isti‘dhaf manifest through educational inequality, the dual burden of domestic and public responsibilities, victim blaming, and the commodification of women’s bodies. The study proposes empowerment strategies based on Qur’anic principles, including spiritual and social hijrah, gender literacy, and inclusive reinterpretation of both texts and policy. By integrating gender-sensitive exegesis with the lived experiences of Indonesian women, this article offers a new framework for Qur’anic gender discourse and supports structural transformation rooted in Islamic justice.